A System for State-of-health Diagnosis of Lead-acid Batteries Integrated with a Battery Charger - Lazzarin, Telles B. (2012)
This paper reports a theoretical and experimental study on a proposal for a lead–acid battery charger applied in UPS, which has an integrated on-line test system to determine the state-of-health (SoH) of the batteries. The charger control structure is designed to ensure an appropriate charge for every battery in the pack. The battery evaluation system is based on historical analysis of the periodic measurements, such as internal impedance, DC voltage and operation temperature, performed for each battery. The periodic monitoring of these parameters provided by the integration of systems eliminates the disadvantages of online tests and thus allows the user to analyze the batteries adequately. The structure was experimentally verified on a prototype, where the battery SoH diagnosis system was integrated with a 1.5 kW battery charger. The system was designed for a bank of sixteen batteries associated in series.